2021
DOI: 10.1182/blood.2020006157
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary α tryptasemia is a valid genetic biomarker for severe mediator-related symptoms in mastocytosis

Abstract: Mastocytosis is a hematopoietic neoplasm characterized by expansion of KIT D816V-mutated clonal mast cells in various organs and severe or even life-threatening anaphylactic reactions. Recently, hereditary α-tryptasemia (HαT) has been described as a common genetic trait with increased copy numbers of the α-tryptase encoding gene, TPSAB1, and associated with an increased basal serum tryptase level and a risk of mast cell activation. The purpose of our study was to elucidate the clinical relevance of HαT in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
166
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(174 citation statements)
references
References 58 publications
4
166
4
Order By: Relevance
“…The correlation between MC mediator levels and presence of MC mediator‐release symptoms (MCMRS) or systemic MC burden remains incompletely understood; in one study of indolent mastocytosis patients, MC mediator levels were significantly correlated with BM MC burden, but not MCMRS 55 . In contrast, mastocytosis patients with HAT demonstrate significantly higher serum tryptase level and frequency of Hymenoptera venom reactions/anaphylaxis, independent of BM MC burden 65 …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between MC mediator levels and presence of MC mediator‐release symptoms (MCMRS) or systemic MC burden remains incompletely understood; in one study of indolent mastocytosis patients, MC mediator levels were significantly correlated with BM MC burden, but not MCMRS 55 . In contrast, mastocytosis patients with HAT demonstrate significantly higher serum tryptase level and frequency of Hymenoptera venom reactions/anaphylaxis, independent of BM MC burden 65 …”
Section: Diagnosismentioning
confidence: 99%
“…Normal MC display a spectrum of “activation levels” in vivo, and the mechanisms governing the secretory phenotype and mediator release patterns are not completely understood 64 . Further, the prevalence of hereditary α‐tryptasemia (HAT), a relatively common genetic trait associated with increased basal serum tryptase level and increased predilection for mast cell activation, has been shown to be significantly higher in mastocytosis patients (17.2%) as compared to normal controls (4.4%) 65 . In SM, a persistently elevated serum tryptase level (>20 ng/ml) counts as a minor diagnostic criterion per the WHO framework 1 ; while the levels vary widely, serum tryptase is elevated in the vast majority of SM patients across all WHO subgroups; a significantly greater proportion of ASM and SM‐AHN patients exhibit a markedly elevated serum tryptase level (>200 ng/ml) compared to those with ISM 10 .…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, hereditary alpha-tryptasemia (HαT) has been described, a genetic trait with duplicated TPSAB1 germline copy numbers leading to elevated basal serum tryptase (60)(61)(62), but also to MC mediator-related symptoms. It can be found in about 5% of unselected healthy individuals (61)(62)(63)(64). The prevalence of certain symptoms related to MC activation has been described to be higher in HαT carriers than in the general population, with urticaria/angioedema in 51%, skin flushing/pruritus in 32-55% and irritable bowel syndrome or food intolerance in28-49% of patients (58,62).…”
Section: Hereditary Alpha-tryptasemia As Risk Factor For Mediator-relmentioning
confidence: 99%
“…The prevalence of HαT was similar in patients with hymenoptera venom allergy with and without mastocytosis, however their clinical reactions were more severe. In a study assessing TPSAB1 germline copy number variants in 180 mastocytosis patients, 180 sex-matched control subjects, 720 patients with other myeloid neoplasms, and 61 additional mastocytosis patients of an independent validation cohort, α-tryptase encoding TPSAB1 copy number gains corresponding to HαT were identified in 17.2% of mastocytosis patients as compared to only 4.4% of the control population (p<0.001) (63). This pronounced difference indicates a possible pathogenic role of TPSAB1 copy number gains in the evolution of mastocytosis.…”
Section: Hereditary Alpha-tryptasemia As Risk Factor For Mediator-relmentioning
confidence: 99%
“…Also reported are connective tissue abnormalities and dysautonomia. Individuals with multiple duplications show higher tryptase levels in serum, are more symptomatic, and have higher risk for severe anaphylaxis 92,93 . Recent mechanistic studies have demonstrated that unique enzymatic properties of alpha-tryptase containing heterotetrameric tryptases may contribute to this association 94 .…”
Section: Mast Cells In Diseasesmentioning
confidence: 99%